Cynics, Paul and the Pauline Churches. - Downing, F. Gerald (Taylor and Francis, 2013)
F. Gerald Downing explores the teachings of Paul, arguing that the development of Paul's preaching and of the Pauline Church owed a great deal to the views of the vagabond Cynic philosophers, critics of the gods and of the ethos of civic society. F. Gerald Downing examines the New Testament writings of Paul, explaining how he would have been seen, heard, perceived and understood by his culturally and ethnically diverse converts and disciples. He engages in a lucid Pauline commentary and offers some startling and ground-breaking views of Paul and his Word. Cynics, Paul and the Pauline.